2017
DOI: 10.1172/jci.insight.90723
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental enrichment on the murine inflammatory immune response

Abstract: Living in a mentally and physically stimulating environment has been suggested to have a beneficial effect on the immune response. This study investigates these effects, utilizing a 2-week program of environmental enrichment (EE) and 2 models of acute inflammation: zymosan-induced peritonitis (ZIP) and the cecal ligation and puncture (CLP) model of sepsis. Our results revealed that following exposure to EE, mice possessed a significantly higher circulating neutrophil to lymphocyte ratio compared with control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…ArtinM capture by the lymphatic system makes possible the lectin to pass through the appropriate circuit for exerting its immunomodulatory effect, while preserving its bioavailability as an immunomodulatory agent and reproducing advantages that were already reported for vaccines and adjuvants [ 36 , 42 , 43 ]. Recently, Broad et al demonstrated that mice maintained in an enriched environment (EE) favors the modulation of their immune response, determined by infecting the mice and verifying that the inflammatory response favors the resolution of the systemic infection [ 44 ]. The immunomodulation induced by EE and ArtinM are similar because both are imperceptible in naïve mice but notable in infected animals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ArtinM capture by the lymphatic system makes possible the lectin to pass through the appropriate circuit for exerting its immunomodulatory effect, while preserving its bioavailability as an immunomodulatory agent and reproducing advantages that were already reported for vaccines and adjuvants [ 36 , 42 , 43 ]. Recently, Broad et al demonstrated that mice maintained in an enriched environment (EE) favors the modulation of their immune response, determined by infecting the mice and verifying that the inflammatory response favors the resolution of the systemic infection [ 44 ]. The immunomodulation induced by EE and ArtinM are similar because both are imperceptible in naïve mice but notable in infected animals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Broad et al demonstrated that mice maintained in an enriched environment (EE) favors the modulation of their immune response, determined by infecting the mice and verifying that the inflammatory response favors the resolution of the systemic infection [ 44 ]. The immunomodulation induced by EE and ArtinM are similar because both are imperceptible in naïve mice but notable in infected animals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This central inflammation is characterized by an increase in the hippocampal expression of proinflammatory cytokines (including IL-1β, IL-6, and TNF-α) and a decrease in the expression of neurotrophic (BDNF and NGF) and neuromodulatory factors. EE attenuates hippocampal neuroinflammation and therefore prevents the plasticity alteration [59][60][61].…”
Section: Effect Of Ee On Hippocampal Plasticitymentioning
confidence: 99%
“…Experimentally induced sickness, through the injection of bacterial toxins, has been shown to diminish structural plasticity, including adult neurogenesis in the hippocampus (Bastos, Moriya, Inui, Katura, & Nakahata, 2008; Fujioka & Akema, 2010), as well as to impair cognitive function (Lee et al, 2008; Valero, Mastrella, Neiva, Sánchez, & Malva, 2014) and increase anxiety-like behavior (Bassi et al, 2012; Savignac et al, 2016). Enriched environment living has been shown to have impacts on the immune system by enhancing its ability to fight infection (Brod et al, 2017) and tumors (Garofalo et al, 2015), as well as diminishing inflammatory effects in certain brain regions (Mlynarik, Johansson, & Jezova, 2004; Williamson et al, 2012). Taken together, these findings suggest complex relationships among enrichment, stress, infection, and hippocampal structure and function, yet questions remain.…”
Section: Introductionmentioning
confidence: 99%